Late rupture of artificial neochordae associated with hemolytic anemia. Issue 4 (October 2017) - Nakaoka, Yoko; Kubokawa, Sho-ichi; Yamashina, Syusuke; Yamamoto, Satoshi; Teshima, Hideki; Irie, Hiroyuki; Kawai, Kazuya; Hamashige, Naohisa; Doi, Yoshinori
Abstract: A 63-year-old man, status post-mitral valve repair for severe mitral regurgitation secondary to ruptured chordae of the anterior leaflet, was admitted seven years after surgery because of a recent history of hematuria. A new apical pansystolic murmur was audible. Hemoglobin level was 5.7 g/dL. Results of other hematologic studies and a peripheral blood smear were indicative of mechanical hemolysis. Transesophageal echocardiography showed a high-velocity jet of mitral regurgitation that directly collided with the annuloplasty ring. At re-operation, one of the artificial neochordae to A2 and A3 segments was found to be disrupted. The mitral valve was replaced with a 33/31 mm On-X valve. Hemolytic anemia disappeared immediately after surgery. Although mitral valve repair with artificial neochodae has been shown to have long-term durability, it should be recognized that artificial neochordae may rupture a long time after mitral valve repair. Also, although hemolytic anemia is known as an early complication after mitral valve repair, it is worth knowing that hemolytic anemia may occur as a late complication after mitral valve repair. Continuous long-term monitoring of the patients after mitral valve repair is recommended. <Learning objectives: Artificial neochordae may at times rupture long period after mitral valve repair. Also, although hemolytic anemia is known as an early complication after mitral valve repair, it may occur as a complication due to late rupture of artificial neochordae. Continuous long-term monitoring of the patient after mitral valve repair is recommended.>